A cluster randomized controlled trial to evaluate the effectiveness of the clinically integrated RHL evidence -based medicine course - Mittal Suneeta; Lumbiganon Pisake; Cecatti Jose G; Germar Maria J; Carroli Guillermo; Gulmezoglu A Metin; Khan Khalid S; Kulier Regina; Pattinson Robert; Wolomby-Molond; Bergh Anne-Marie; May Win (BMC, 2010)
Abstract Background and objectives Evidence-based health care requires clinicians to engage with use of evidence in decision-making at the workplace. A learner-centred, problem-based course that integrates e-learning in the clinical setting has been developed for application in obstetrics and gynaecology units. The course content uses the WHO reproductive health library (RHL) as the resource for systematic reviews. This project aims to evaluate a clinically integrated teaching programme for incorporation of evidence provided through the WHO RHL. The hypothesis is that the RHL-EBM (clinically integrated e-learning) course will improve participants' knowledge, skills and attitudes, as well as institutional practice and educational environment, as compared to the use of standard postgraduate educational resources for EBM teaching that are not clinically integrated. Methods The study will be a multicentre, cluster randomized controlled trial, carried out in seven countries (Argentina, Brazil, Democratic Republic of Congo, India, Philippines, South Africa, Thailand), involving 50-60 obstetrics and gynaecology teaching units. The trial will be carried out on postgraduate trainees in the first two years of their training. In the intervention group, trainees will receive the RHL-EBM course. The course consists of five modules, each comprising self-directed e-learning components and clinically related activities, assignments and assessments, coordinated between the facilitator and the postgraduate trainee. The course will take about 12 weeks, with assessments taking place pre-course and 4 weeks post-course. In the control group, trainees will receive electronic, self-directed EBM-teaching materials. All data collection will be online. The primary outcome measures are gain in EBM knowledge, change in attitudes towards EBM and competencies in EBM measured by multiple choice questions (MCQs) and a skills-assessing questionniare administered eletronically. These questions have been developed by using questions from validated questionnaires and adapting them to the current course. Secondary outcome measure will be educational environment towards EBM which will be assessed by a specifically developed questionnaire. Expected outcomes The trial will determine whether the RHL EBM (clinically integrated e-leraning) course will increase knowledge, skills and attitudes towards EBM and improve the educational environment as compared to standard teaching that is not clinically integrated. If effective, the RHL-EBM course can be implemented in teaching institutions worldwide in both, low-and middle income countries as well as industrialized settings. The results will have a broader impact than just EBM training because if the approach is successful then the same educational strategy can be used to target other priority clinical and methodological areas. Trial Registration ACTRN12609000198224